The routine of the street outreach office team: Procedures and care for the homeless - Fonseca Viegas, Selma Maria da; Nitschke, Rosane Goncalves; Tholl, Adriana Dutra; Bernardo, Lucas Andreolli; Potrich, Tassiana; Arcaya Moncada, Maria Josefa; Nabarro, Marta (My University, 2021)
This study aims to understand the routine of the street outreach office team regarding the attention paid to the homeless. It is a holistic qualitative multiple case study, based on Michel Maffesoli's Comprehensive and Quotidian Sociology. It was performed using two key informants and 20 professionals of the street outreach office of two capitals in the South of Brazil. For data analysis, we used the Thematic Content Analysis.The itinerancy, the unexpected and the immediacy of homeless people are part of the team's everyday life. The potentialities of the teams are their intra- and intersectoral networks; inter- and transdisciplinarity; and available material/diagnostic resources, whereas the limitations are their inequalities, vulnerabilities and social exclusion, in addition to the specificities of the homeless and the multiple problems that these people live with. Understanding the routine of the street outreach office reveals co-responsibility in unique actions aligned with the needs of the homeless, precisely signalling that health care needs to be integrated into a network so that these individuals can meet the complex challenges of living in unsafe street environments.
Keywords: the homeless; primary health care; needs and demands in health care; nursing; everyday activities